(untitled) (Al-Academy, 2019)
Employing the social personalities (celebrities) in all fields (artistic, sports, media, etc.) is an important media and visual communication means of identification for the companies and institutions in order to convey the advertising idea in accordance with the creative, aesthetic and functional principles aimed at promoting products and gaining the symbolic value for the company. This study investigates the employment of social personalities in the commercial advertising design in order to pinpoint the importance of employing celebrities and their representation in the advertisement to convey the meaning that signifies the advertisement goal. Thus the question of the study is: "What are the mechanisms of employing celebrities in the design of commercial advertising?" The importance of the research is its contribution to guide the employment of celebrities to the relevant parties. The aim of the research is to identify the mechanisms of employing the celebrities in the advertisement design. The research time limits extend from 2016 to 2017, with the selection of Asia cell and Zain Iraq as a field for the study. The theoretical framework contains a section which is (the functionality of commercial advertising). The research procedures included clarifying the method used by the researcher which is the descriptive approach used in order to reach the results, conclusions, recommendations and proposals. The results mentioned that: The employment of celebrities in the advertising is an interaction with the recipient, that when most recipients are exposed to the advertisement they are not ready to actually buy the product so it is important to get the information of this product stored in their memory in order that the situation would be convincing to buy, thus recalling the information that was announced. The celebrity employment strategy is considered the most successful way to achieve the goal of the commercial advertisement. The researcher, through the results , reached at a conclusion that : celebrities in advertising represent products, companies or enterprises and draw a positive mental image of the product or service and link the beauty and credibility of the personality to the qualities of the product and create positive and lovely tendencies in the minds of recipients towards the advertisement.